SUSTAINABLE MANAGEMENT OF TOURISM IN PANDEMIC COVID-19 - Senny Luckyardi; Eddy Soeryanto Soegoto; Theresia Valentina Lumban Gaol; Dina Oktafiani (FIRM Journal of Management Studies, 2021)
Currently, Tourism is an inseparable part of life in modern society. Tired with routine urban activities, triggering the development of nature tourism as a place of recreation that is most in demand. Therefore, this research was conducted to determine the role of community participation and land-use change in the Kampoeng Ciherang Tourism Area, to realize sustainable tourism management in the Covid-19 pandemic. The method used in this research was data collection using primary and secondary data, by directly observing the current conditions of Kampoeng Ciherang Tourism Area, which was supported by the availability of secondary data from the relevant agencies. This research discussed community participation in the management of Kampoeng Ciherang Tourism Area, and the impact on land use from tourism activities, especially during the Covid-19 pandemic. The results of this study indicated that in managing tourism, the Tourism Area of Kampung Ciherang had not been able to realize sustainable tourism management especially during the Covid-19 pandemic period, this could be seen from the low level of community participation because tourism management was still fully held by the private sector as the owner of facilities and infrastructure and government as supervisors, even though the change in land use did not experience significant changes at the tourist site. If it does not pay attention to sustainable tourism management, it is feared that in the future there will be an uncontrolled conversion of land from these activities.